2015
DOI: 10.1016/j.devcel.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune Regulation of Mammary Postnatal Organogenesis

Abstract: SUMMARY Postnatal organogenesis occurs in an immune competent environment and is tightly controlled by interplay between positive and negative regulators. Innate immune cells have beneficial roles in postnatal tissue remodeling, but roles for the adaptive immune system are currently unexplored. Here we show that adaptive immune responses participate in the normal postnatal development of a non-lymphoid epithelial tissue. Since the mammary gland (MG) is the only organ developing predominantly after birth, we ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 52 publications
(72 reference statements)
2
78
0
1
Order By: Relevance
“…Th1 cells have been shown to play a direct role both in premalignant immune surveillance (64) and active control of postnatal mammary organogenesis and epithelial rearrangement (65). These data support the increased T-bet we detected in benign breast tumors compared with mammary reduction tissues (in the absence of the increased proportion of FOXP3 + CD4 + T cells seen in invasive tumors).…”
Section: Discussionsupporting
confidence: 79%
“…Th1 cells have been shown to play a direct role both in premalignant immune surveillance (64) and active control of postnatal mammary organogenesis and epithelial rearrangement (65). These data support the increased T-bet we detected in benign breast tumors compared with mammary reduction tissues (in the absence of the increased proportion of FOXP3 + CD4 + T cells seen in invasive tumors).…”
Section: Discussionsupporting
confidence: 79%
“…Several groups revealed that lymphocytes drive initial myeloid cell programming to foster chronic inflammation in a tissue-specific manner. For example, during mammary branching morphogenesis and ductal carcinogenesis, cytokines derived from T H 2-CD4 + T cells, e.g., IL-4 and -13, activate macrophages and monocytes infiltrating mammary tissue (DeNardo et al, 2009; Plaks et al, 2015). In neoplastic scenarios, signaling downstream of IL-4 receptors on monocytes and macrophages triggers protumorigenic T H 2 gene-expression programs that activate tissue-remodeling cascades, via expression and activation of cathepsin proteases, and immune-suppressive programs, via upregulation of IL-10 and immune-checkpoint molecules (DeNardo et al, 2009; Gocheva et al, 2010; Mitchem et al, 2013; Ruffell et al, 2014).…”
Section: Chronic Inflammation and Alterations Of Leukocyte Compartmenmentioning
confidence: 99%
“…Branching morphogenesis of an epithelial tree within the fat pad requires epithelial cell proliferation and apoptosis, and remodeling of the surrounding stroma to allow ductal invasion and expansion [1]. Cells of both the innate and adaptive branches of the immune system have been implicated or proven to play important roles in normal mammary gland development and involution [2,3]. This is most dramatically illustrated by postnatal ablation of hematopoietic cells, which results in a block of mammary development that can be rescued by bone marrow transplantation [4].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, macrophages, eosinophils and mast cells are crucial to the formation of a branched ductal tree [5,6,2], but are also important players during further development in pregnancy and during involution [6,7]. A specific subset of T cells, in collaboration with antigen-presenting cells, is also a negative regulator of postnatal mammary gland organogenesis [3]. …”
Section: Introductionmentioning
confidence: 99%